OsGRF4AA compromises heat tolerance of developing pollen grains in rice - Mo, Yujian; Li, Guangyan; Liu, Li; Zhang, Yingjie; Li, Junyi; Yang, Meizhen; Chen, Shanlan; Lin, Qiaoling; Fu, Guanfu; Zheng, Dianfeng; Ling, Yu (Frontiers in Plant Science, 2023)
Abstract Extreme high temperature at meiosis stage of rice would cause severe decrease in spikelet fertility and grain yield. The rice variety GRAIN SIZE ON CHROMOSOME 2 (GS2) contains sequence variations of OsGRF4 (OsGRF4AA), escaping the miR396-mediated degradation of this gene at mRNA level. Accumulation of OsGRF4 enhances nitrogen usage and metabolism, and increases grain size and grain yield. Here, we found that pollen viability and seed-setting rate of GS2 decreased more seriously under heat stress (HS) than its background Zhonghua 11 (ZH11). Transcriptomic analysis revealed that genes related to carbohydrate metabolic process were expressed and regulated differentially by HS in anthers of GS2 and ZH11. Moreover, expressions of genes handling chloroplast development and photosynthesis, lipid metabolisms and key transcription factors, including 8 male sterile genes, were inhibited to more extents by HS in GS2. Interestingly, pre-mRNAs of OsGRF4 itself and a group of essential genes involved in development and fertilization were differentially spliced in anthers from GS2 and ZH11. Taken together, our results suggest that OsGRF4 variation affects proper transcriptional and splicing regulations of genes under HS, which could be mediated by, and also feedback to carbohydrate and nitrogen metabolisms, resulting in reduction of heat tolerance of rice anther consequently.